PENGARUH PRICE EARNING RATIO, DIVIDEND PAYOUT RATIO, IRETURN ON ASSETS, TINGKAT SUKU BUNGA SBI, SERTA KURS DOLLAR AS TERHADAP HARGA SAHAM - Dewi, Gusti Ayu Ketut Chandni; Sudiartha, Gede Merta (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
ABSTRACT Activities related to the supply and demand in the securities of public companies that are associated with the securities issued by the company is called the capital market. The purpose of this study to determine the effect of micro and macro factors on stock prices as Price Earning Ratio, Dividend Payout Ratio, Return on Assets, SBI interest rate, and the U.S. dollar exchange rate. The research sample was taken 7 companies on manufacturing companies in Indonesia Stock Exchange. using purposive sampling method. Data collection is done by analyzing the annual financial statements. Through multiple linear regression analysis, the analysis showed that simultaneous variables Price Earning Ratio, Dividend Payout Ratio, Return on Assets, Rate Interest Rates and the U.S. Dollar exchange rate together simultaneously affect stock price. As well as partial Price Earning Ratio, Dividend Payout Ratio and significant negative effect on stock prices. SBI Interest Rates menunujukkan that the positive and significant effect on stock prices. As well as no effect on stock prices is Return On Assets and U.S. Dollar exchange rate. These results may indicate that the investor in making an investment decision must consider the variables that affect the stock price. Keywords : Price Earning Ratio, Dividend Payout Ratio, Return on Assets, Rate Interest Rates, U.S. Dollar exchange rate, stock price index